2015
DOI: 10.1007/s13224-015-0775-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Granulocyte Colony-Stimulating Factor (GCSF) on Persistent Thin Endometrium in Frozen Embryo Transfer (FET) Cycles

Abstract: Objective To predict the effectiveness of granulocyte colony-stimulating factor (GCSF) in the treatment of persistent thin endometrium resistant to other treatments in frozen embryo transfer (FET) cycles. Study Design This is a hospital-based prospective study. Patients Thirty-five women with persistent thin endometrium (\7 mm) resistant to standard treatments were involved in this study. Intervention(s) Intrauterine infusion of GCSF (300 mcg/ 1 ml) was done in patients with thin endometrium on day 14 of FET c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
2
13
0
1
Order By: Relevance
“…These findings are similar to other studies. 5,9 Hence from this study it is observed that injection GCSF when given at the level of fundus caused an increase in the incidence of ectopic gestation probably because of the spillage into the tubes from fundus. Only 1 patient had missed abortion when GCSF was instilled above the level of the internal os.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…These findings are similar to other studies. 5,9 Hence from this study it is observed that injection GCSF when given at the level of fundus caused an increase in the incidence of ectopic gestation probably because of the spillage into the tubes from fundus. Only 1 patient had missed abortion when GCSF was instilled above the level of the internal os.…”
Section: Discussionmentioning
confidence: 55%
“…5,7 G-CSF is predictive of IVF outcome, it is a biomarker for oocyte/embryos with implantation potential, reduces unexplained repeated pregnancy loss and plays a role in the genesis of early endometriotic lesions, and suppresses autoimmunity. [8][9][10] Administration of G-CSF does not seem to affect embryonic chromosomal constitution and therefore seems safe. Some studies have shown that systemic administration of G-CSF in patients with recurrent spontaneous pregnancy losses and repetitive implantation failures improves pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the women underwent intrauterine infusion of G-CSF (300 mg/ 1 ml) on the day 14 of the cycle and endometrium was measured 2 days later. 35 A total of 16 patients had cancellation of cycle due to inadequate endometrial thickness and three patients (15.78%) had biochemical pregnancies.…”
Section: Recombinant G-csf For Treatment Of Thin Endometrium In Art: mentioning
confidence: 99%
“…В процессе имплантации участвуют иммунологические механизмы в эндометрии. GCSF повышает секрецию эндогенных цитокинов [17]. Исследование T. Tanaka и соавт.…”
Section: гранулоцитарный колониестимулирующий фактор и его влияние наunclassified